A Study on Cloud Computing in E-Governance - Mounika, Kondra; Taduri, Anusha; Manda, Sridhar (International Journal of Computer Sciences and Engineering, 2025)
A technique Cloud computing is for registering which is planned from the improvement of advances for parallel computing, cloud computing, and service-oriented architecture. What's more, its point is to give correspondence and capacity assets in an ensured situation to convey the services as quick as could be allowed, which is given through Internet stage. The given Services in e-government are accessible through Internet, along these lines cloud computing can be utilized as a part of the usage of Egovernmence design and furnish better service with the most reduced cost utilizing its advantages. In this examination, the cloud computing in e-government has been clarified and it's been endeavored to distinguish the difficulties and advantages of the cloud to show signs of improvement condition to actualize new innovation.